2017
DOI: 10.5588/ijtld.17.0232
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 ligands in pleural fluid as markers for the diagnosis of tuberculous pleural effusion

Abstract: Levels of CXR3 ligands in pleural effusion are useful for diagnosing TPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…The researchers enrolled 336 subjects with PE (106 TPE and 230 non-TPE) and simultaneously evaluated the diagnostic accuracy of ADA, IFN-γ, CXCL9, and CXCL11. They found that these four markers had comparable diagnostic accuracy, with AUCs all higher than 0.95 (68).…”
Section: C-x-c Motif Chemokine Receptor 3 (Cxcr3) Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers enrolled 336 subjects with PE (106 TPE and 230 non-TPE) and simultaneously evaluated the diagnostic accuracy of ADA, IFN-γ, CXCL9, and CXCL11. They found that these four markers had comparable diagnostic accuracy, with AUCs all higher than 0.95 (68).…”
Section: C-x-c Motif Chemokine Receptor 3 (Cxcr3) Ligandsmentioning
confidence: 99%
“…Thus far, only one study has investigated the diagnostic accuracy of CXCL9 and CXCL11 for TPE (68). The researchers enrolled 336 subjects with PE (106 TPE and 230 non-TPE) and simultaneously evaluated the diagnostic accuracy of ADA, IFN-γ, CXCL9, and CXCL11.…”
Section: C-x-c Motif Chemokine Receptor 3 (Cxcr3) Ligandsmentioning
confidence: 99%
“…CXCL11, as a biomarker of TB, has been widely studied. However, for patients with ST, the expression levels of CXCL9 and CXCL10 are poorly understood (11).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical testing of body uid has been widely performed in the differential diagnosis between transudate and pathological pleural effusions. Though traditional biomarkers, such as ADA, LDH, glucose, protein, have been applied and new markers like IL-27 [29], IFN-γ [30], CXCL9 and CXCL11 [31] are been developing, ADA is still the most cost-effective pleural uid marker. However, its value is questioned in antidiastole and a low prevalence setting.…”
Section: Discussionmentioning
confidence: 99%